Murder and Media in the New Rome - Simpson, T. author. aut Link
XII, 264 p.
Keywords: An insightful look into the origins of modern Italian media culture by examining a sensational crime and trial that took place in Rome in the late 1870s, when a bloody murder triggered a national spectacle that became the first great media circus in the new nation of Italy, crucially shaping the young state's public sphere and image of itself.